2016
DOI: 10.2298/abs151111011v
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale variations in leaf shape under anthropogenic disturbance in dioecious forest forb mercurialis perennis: A geometric morphometric examination

Abstract: Plants are exposed to increasing levels of diverse human activities that have profound effects on their overall morphology and, specifically, on leaf morphology. Anthropogenic disturbances in urban and suburban forest recreational sites are attracting growing research interest. To explore the persisting recreational impact on leaf shape and size, we conducted a field study on the dioecious forb Mercurialis perennis L. (Euphorbiaceae), typical for undisturbed understory communities. We selected adjacent sites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In species where males exhibit greater total aboveground biomass, longer shoots and bigger leaves, these traits can make them more apparent, conferring greater susceptibility to herbivores, especially to folivores [21]. Previous research found prominent male-biased SSD in height in M. perennis populations at lower altitudes [34,52]; however, this difference tended to decrease with increasing altitude [34]. In the present study, at the upper limit of altitudinal distribution, no significant effect of sex on plant height or total leaf area was found.…”
Section: Differences Between Sexes In Contrasting Light Environmentsmentioning
confidence: 99%
“…In species where males exhibit greater total aboveground biomass, longer shoots and bigger leaves, these traits can make them more apparent, conferring greater susceptibility to herbivores, especially to folivores [21]. Previous research found prominent male-biased SSD in height in M. perennis populations at lower altitudes [34,52]; however, this difference tended to decrease with increasing altitude [34]. In the present study, at the upper limit of altitudinal distribution, no significant effect of sex on plant height or total leaf area was found.…”
Section: Differences Between Sexes In Contrasting Light Environmentsmentioning
confidence: 99%
“…In the case of clonal plants occurring in the undergrowth, human trampling can trigger mechanical stress and reduction of sexual reproduction through damage to flowering stems and/or impact on the number and dimensions of leaves. This was observed in populations of Anemone nemorosa L. [62] and Mercurialis perennis L. [63]. Moreover, human trampling and soil digging by dogs accompanying humans can contribute to genet fragmentation and vegetative propagation of species creating thin and delicate connections between ramets such as Fragaria vesca L. [64], Maianthemum bifolium (L.) F.W.…”
Section: The Effect Of Informal Tourist Trails On Plant Cover Traitsmentioning
confidence: 99%
“…The double fan method is employed by Vujic et al. () based on two locked landmarks. Thus, the fan is adjusted in size to the leaf and a second axis is not needed.…”
Section: Introductionmentioning
confidence: 99%
“…A single fan with just one axis would not keep the same proportions and thus the semilandmarks would slide around. The double fan method is employed by Vujic et al (2016) based on two locked landmarks. Thus, the fan is adjusted in size to the leaf and a second axis is not needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation